A preliminary study on the molecular variabilities in Varroa destructor and its effect on the body measurements - Kesik, Harun Kaya; Kilinc, Seyma Gunyakti; Celik, Figen; Gul, Abdurrahman; Simsek, Sami (Springer, 2024)
Varroa species, commonly known as the honey bee mites, poses a significant challenge to the worldwide beekeeping industry. The aim of this study was to investigate the effect of haplotype variation on morphology of Varroa destructor. Forty-one apiaries across Bingol province (T & uuml;rkiye) and its districts were visited using random sampling to examine 2440 honey bee colonies. Adult Varroa spp mites were collected from each apiary and morphometrically analysed at species level, resulting in seven mites being used to represent each apiary. Length measurements were taken of six morphometric parameters of 287 adult Varroa spp. isolates under a stereo microscope, including body length, body width, genital shield length, genital shield width, anal shield length and anal shield width. In order to analyze genetic diversity, genomic DNA was isolated from a total of 82 individual Varroa spp. isolates, and specific primers were used to amplify the mitochondrial cytochrome oxidase subunite 1 (mt-CO1) gene fragment (376 bp) by PCR followed by DNA sequence analysis. Morphometric analysis revealed that the adult Varroa spp isolates had a body width of 1691.10 +/- 06.55 mu m and a body length of 1125.69 +/- 06.62 mu m, with no significant differences between apiaries. These findings indicate that all the isolates were morphometrically identified as V. destructor. Moreover, all the sequences were highly similar to the Korean (K) haplotype of V. destructor. Six haplotypes (Hap01-Hap06) of V. destructor were identified via haplotype analysis. The haplotype groups exhibited low nucleotide diversity and were separated by 1-3 point mutations. There was no significant difference in body widths between Hap01 and other haplotypes. However, Hap03 had significantly higher body widths than Hap04 and Hap05. This indicates that haplotype differences may have an effect on morphological parameters in Varroa species.
Keywords: Varroa destructor; Honey bee; Mt-CO1; PCR; Haplotype